Specialized Plant Metabolism Characteristics and Impact on Target Molecule Biotechnological Production - Matsuura, Hélio Nitta; Malik, Sonia; de Costa, Fernanda; Yousefzadi, Morteza; Mirjalili, Mohammad Hossein; Arroo, Randolph; Bhambra, Avninder S; Strnad, Miroslav; Bonfill, Mercedes; Fett-Neto, Arthur Germano (Molecular biotechnology, 2018)
Plant secondary metabolism evolved in the context of highly organized and differentiated cells and tissues, featuring massive chemical complexity operating under tight environmental, developmental and genetic control. Biotechnological demand for natural products has been continuously increasing because of their significant value and new applications, mainly as pharmaceuticals. Aseptic production systems of plant secondary metabolites have improved considerably, constituting an attractive tool for increased, stable and large-scale supply of valuable molecules. Surprisingly, to date, only a few examples including taxol, shikonin, berberine and artemisinin have emerged as success cases of commercial production using this strategy. The present review focuses on the main characteristics of plant specialized metabolism and their implications for current strategies used to produce secondary compounds in axenic cultivation systems. The search for consonance between plant secondary metabolism unique features and various in vitro culture systems, including cell, tissue, organ, and engineered cultures, as well as heterologous expression in microbial platforms, is discussed. Data to date strongly suggest that attaining full potential of these biotechnology production strategies requires being able to take advantage of plant specialized metabolism singularities for improved target molecule yields and for bypassing inherent difficulties in its rational manipulation.
Keywords: artemisininy; Berberine; Plants; Phytochemicals; fytonutrienty; axenická kultura; Metabolic Engineering; biotechnologie; Tissue Culture Techniques; buněčné kultury; Secondary Metabolism; Secondary metabolites; Synthetic biology; paclitaxel; Genetically engineered cultures; In vitro culture; naftochinony; techniky tkáňových kultur; Biological Products; Paclitaxel; rostliny; rostlinné buňky; Artemisinins; berberin; Biotechnology; Cell Culture Techniques; Plant Cells; Natural products; metabolické inženýrství; Naphthoquinones; sekundární metabolismus; biologické přípravky; Axenic Culture